Respiratory health of patients receiving agonist opioid treatment: Gender differences. - Nelson, P.; Bartu, Anne; Bill Musk, A.; Aboagye-Sarfo, P. (AU-CNS Onlus, 2016)
Background: The recommended treatment for opioid dependent people is agonist opioid treatment (AOT). The pharmacotherapies used are methadone and buprenorphine. The effects of methadone are similar to other opioids such as morphine and include sedation and respiratory depression. There is good evidence that polydrug use, particularly tobacco, cannabis and alcohol, is common among opioid dependent people on AOT programs. These drugs have also been linked to impaired lung function. The aims were to examine gender differences in (a) tobacco and cannabis consumption, and (b) respiratory symptoms and lung function of opioid dependent people receiving AOT. Methods: The sample (n=149) were recruited from two Western Australian drug and alcohol clinics from March 2009 to July 2012 from a pool of ~350 patients receiving AOT. Data were obtained on current and past smoking, passive smoking, cannabis use, AOT medications, asthma, and respiratory symptoms. Forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC) and the FEV1/FVC ratio were measured by spirometry. Results: Mean age ~40. Smoking prevalence (tobacco) was 89% males and 82% females, cannabis 47% males and 54% females. Over 60% were unemployed. The majority were treated with methadone. Breathlessness was associated with FEV1 (p=0.02) and FVC (p=0.02), asthma with FEV1 (p=0.04). COPD was detected in 27% of males and 24% of females. 51% reported shortness of breath when hurrying on level ground or walking up a slight hill and 30% gave a history of morning cough. As indicated by the FEV/FVC ratio <0.70, 27.3% of men and 24 % of women had COPD. Conclusions: The sample was relatively young but many men and women were exhibiting smoking related respiratory symptoms and ~25% had COPD. Declining lung function appears to be an important morbidity among patients on OST, particularly among women. Smoking cessation interventions should be included in AOT regimes.